Strengthening Community Waste Management Through the ASRI Program in East Java, Indonesia - Eka Sudi Rahmawati Putri; Farah Rizki Aprilia; Valdi Deva Putra; Damai Arum Pratiwi (Jurnal Ilmiah Global Education, 2026)
The ASRI (Aksi Semanding Sadar Lingkungan) program was developed as a solution to the problem of waste management in Semanding Village, Kauman District, Ponorogo Regency. The habit of burning waste in this village is caused by the lack of education about the negative impacts of burning and the lack of waste management facilities. The ASRI program takes a partnership approach between Semanding Village and Maesojennar Waste Bank, which receives support from village officials and relevant stakeholders to increase awareness and practice of waste segregation. A series of ASRI programs including socialization, Focus Group Discussion (FGD), pre-test and post-test, and behavior change monitoring were carried out from January 8, 2025 to January 24, 2025 as an intensive activity phase, and continued with follow-up monitoring for the next six months to ensure the sustainability of changes in community behavior related to waste management. The results of the program showed that 75% of the socialization participants understood the negative impact of burning waste, and 15 out of 20 monitored households successfully implemented waste segregation. The program also began to provide economic benefits to the community through the sale of segregated waste. The sustainability of the program can be improved by expanding partnerships, improving waste management facilities, and implementing village policies that support sustainable waste management.